2021
DOI: 10.2174/1871529x22666211221152546
|View full text |Cite
|
Sign up to set email alerts
|

Association of Stress Hyperglycemia and Adverse Cardiac Events in Acute Myocardial Infarction - A Cohort Study

Abstract: Background: Stress hyperglycemia is a common phenomenon in patients presenting with acute myocardial infarction (MI). We aim to evaluate the association of stress hyperglycemia at the time of hospital presentation and adverse cardiac events in myocardial infarction during the course of hospital stay. Methods: Subjects with age ≥18 years with acute MI were recruited on hospital admission and categorized based on admission blood glucose (<180 and ≥180 mg/dl, 50 patients in each group). Both groups were com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The study showed an elevated incidence of complications such as arrhythmias, cardiogenic shock, progression to severe heart failure, and a significant increase in mortality. Hence, SIH in patients with MI had a critical role in the outcome [ 43 ]. Chen et al studied the sequelae in elderly patients with AMI with SIH by determining the association between stress hyperglycemic ratio (SHR) and in-hospital outcomes in elderly patients with AMI.…”
Section: Reviewmentioning
confidence: 99%
“…The study showed an elevated incidence of complications such as arrhythmias, cardiogenic shock, progression to severe heart failure, and a significant increase in mortality. Hence, SIH in patients with MI had a critical role in the outcome [ 43 ]. Chen et al studied the sequelae in elderly patients with AMI with SIH by determining the association between stress hyperglycemic ratio (SHR) and in-hospital outcomes in elderly patients with AMI.…”
Section: Reviewmentioning
confidence: 99%